Analysis Of Student Mathematics Problem Solving Ability Reviewed from Adversity Quotient (Aq) With Dynamic Assessment (Universitas Negeri Semarang, 2022)
This study aims to analyze problem solving skills in terms of Adversity Quotient (AQ) in solving problems of material relations functions. This research was conducted with qualitative research methods. The research subjects were taken by two students from each AQ category in class VIIIA. Data collection techniques using written methods and interviews. The validity of the data used the triangulation method, by comparing the written test data and interviews obtained at different times. The data analysis technique was carried out in 3 stages, namely: data reduction, data presentation, and drawing conclusions. The analytical framework was developed by the researcher based on the stages of problem solving according to Gagne Polya. The research subject selection technique is purposive sampling where the subject is selected based on the students' AQ. The analysis conducted in this study yielded the following results: (1) Students in the AQ quitter category have not been able to carry out problem-solving skills coherently and systematically, the subject can only do good solving skills at the stage of implementing the plan, (2) Students in the AQ camper category are able to carry out their abilities. problem solving well and systematically, although they have not carried out the re-examination stage and have not written down all the things that are known and asked in the problem, (3) AQ climber category students are able to carry out problem solving skills well and systematically from the initial stage to the final stage of problem-solving skills. mathematical problems, (4) Problem solving ability in terms of AQ, namely students in the quitter, camper, and climber categories who have implemented problem solving skills at each stage. Quitter students give up more easily in solving problems than camper and climber students so that the impact on problem solving skills obtained will be different.